EVALUASI KONDISI HUTAN BERDASARKAN KERAGAMAN KUMBANG SUNGUT PANJANG (COLEOPTERA, CERAMBYCIDAE) 1 DI KAWASAN GUNUNG SLAMET - Woro Anggraitoningsih Noerdjito (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Evaluation of forest conditions using longhorn beetles (Coleoptera: Cerambycidae) fauna have been carried out at 3 parts of Mt. Slamet which are, northern part through Guci, southern part through Kalipagu, Baturraden and easthern part through Bambangan. In northern parts, research activities were conducted at about 1200-2500m above sea level (m.asl.), in southern part, research activities was conducted at about 700-1000m m.asl and in eastern part research activities was conducted at about 1500-2400m asl.Out of the 37 species of longhorn beetles were collected during this research, dominated by Sybra fuscotriangularis (55 specimens). The longhorn beetles collected in southern part, indicated lowest individual number (36 spesimen) but indicating hightest species number. In the contrary, the highest number of spesimens collected but lowest species number (10 species) was collected in the eastern part, while in northern part, it was collected 86 individu (17 species).The species compositions and the number of individuals of longhorn beetles collected from each parts (northern, southern and easthern part) were different with specific groups. Longhorn beetles species collected from secondary forest was similar to the primary forest.Distribution pattern of longhorn beetles in Mt. Slamet indicated that some forest species were found at certain altitude such as Batocera spp and Gnoma thomsoni which only found at 700-1000m asl. The forest area which this altitute (700-1000m asl.) was located at the southern part of Mt Slamet (Kalipagu, Baturraden) where known as the main support of water reservoir for electric power and seven spout water (Pancuran Tujuh). Thus this area has to be conserved from illegal logging and human activities.